Effect of long-term application of mineral fertilizers and FYM on microbial dynamics, yield and quality of FCV tobacco (Nicotiana tabacum) grown in vertisols - SUBHASHINI, D V; P, HARISHU KUMAR (The Indian Journal of Agricultural Sciences, 2019)
A long term manurial experiment (Permanent Manurial Trial) with the objective to study the effect of continuous application of organic manure (FYM) and inorganic fertilizers (NPK) on microbial diversity, yield and quality of Flue-cured Virginia (FCV) tobacco (Nicotiana tabacum L. ) as monocrop was carried out at CTRI Farm, Katheru, for 53 years commencing from 1956-57 to 2008-09. The results obtained before the closing of the experiment (2003- 2008) are discussed in this paper. The microbial dynamics expressed in terms of culturable microbial populations, i.e. bacteria, fungi, actinomycetes, Azotobacter and PSB were measured after 53 years of continuous application of mineral fertilizers and organic amendments to vertisols. The population of bacteria, actinomycetes, Azotobacter and PSB were maximum in plots treated with mineral fertilizers and FYM while fungal population was maximum in mineral fertilizers treated plots. The population of bacteria, actinomycetes, Azotobacter and PSB increased in the treatments with the addition of P and K fertilizers alone or in combination. The fungal population decreased with the addition of NPK along with the FYM. Bacillus, Pseudomonas species of bacteria and Trichoderma, Aspergillus and Rhizopus species of fungi, Streptomyces species of actinomycetes were the main dominating culturable microorganisms in all the treatments. The FYM amended plots sustained crop productivity and microbial populations at higher levels than rest of the mineral fertilizer treatments. The average cured leaf yields indicated that only farm yard manure and inorganic nitrogen application has exerted pressure in increasing the cured leaf yields by 24. 52% and 26. 97% respectively in VT-1158 variety of tobacco in vertisols. The nitrogenous fertilizers alone had the most deleterious effect on crop productivity and the biological soil environment. The results of the present study support the concept of balanced fertilization and integrated nutrient management practices for improving the soil quality and sustained crop productivity.